Cross-specificity of protective human antibodies against Klebsiella pneumoniae LPS O-antigen - Rollenske, Tim; Szijarto, Valeria; Lukasiewicz, Jolanta; Guachalla, Luis M.; Stojkovic, Katarina; Hartl, Katharina; Stulik, Lukas; Kocher, Simone; Lasitschka, Felix; Al-Saeedi, Mohammed; Schröder-Braunstein, Jutta; von Frankenberg, Moritz; et al. (Nature immunology, 2018)
Humoral immune responses to microbial polysaccharide surface antigens can prevent bacterial infection but are typically strain specific and fail to mediate broad protection against different serotypes. Here we describe a panel of affinity-matured monoclonal human antibodies from peripheral blood immunoglobulin M–positive (IgM + ) and IgA + memory B cells and clonally related intestinal plasmablasts, directed against the lipopolysaccharide (LPS) O-antigen of Klebsiella pneumoniae , an opportunistic pathogen and major cause of antibiotic-resistant nosocomial infections. The antibodies showed distinct patterns of in vivo cross-specificity and protection against different clinically relevant K. pneumoniae serotypes. However, cross-specificity was not limited to K. pneumoniae , as K. pneumonia e–specific antibodies recognized diverse intestinal microbes and neutralized not only K. pneumoniae LPS but also non– K. pneumoniae LPS. Our data suggest that the recognition of minimal glycan epitopes abundantly expressed on microbial surfaces might serve as an efficient humoral immunological mechanism to control invading pathogens and the large diversity of the human microbiota with a limited set of cross-specific antibodies. Carbohydrate-specific antibodies are typically thought to be of low affinity and produced by T cell–independent pathways. Wardemann and colleagues identify human memory B cells that can produce specific ‘affinity-matured’ antibodies to the O antigen of Klebsiella lipopolysaccharides.